2017
DOI: 10.1097/mib.0000000000001007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Early Surgery and Immunosuppression on Crohnʼs Disease Disabling Outcomes

Abstract: Although neither early surgery nor immunosuppression seem to be able to prevent global disabling disease, an early start of immunosuppression by itself is associated with fewer surgeries and should be considered in daily practice as a preventive strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…Even though some observational studies showed no benefits, [ 4 , 19 , 37 , 39 , 42 ] 1 meta-analysis [ 5 ] and other observational studies did show benefit of early use in reducing CD-related surgeries. [ 11 , 17 , 18 , 20 , 23 , 32 , 34 , 38 , 40 , 43 ] In this cohort, we performed subgroup analysis to determine this effect. To ensure the benefits of thiopurines, only those who took the medicine for at least 3 months were included.…”
Section: Discussionmentioning
confidence: 99%
“…Even though some observational studies showed no benefits, [ 4 , 19 , 37 , 39 , 42 ] 1 meta-analysis [ 5 ] and other observational studies did show benefit of early use in reducing CD-related surgeries. [ 11 , 17 , 18 , 20 , 23 , 32 , 34 , 38 , 40 , 43 ] In this cohort, we performed subgroup analysis to determine this effect. To ensure the benefits of thiopurines, only those who took the medicine for at least 3 months were included.…”
Section: Discussionmentioning
confidence: 99%
“…The cumulative probability of remaining free of CD‐related bowel surgery at 5 years was less than 15% in patients receiving AZA > 36 months, that is, lower than the previous studies . Interestingly, a recent multicentric and retrospective study with 754 patients showed that an early start of immunosuppression (< 6 months) is associated with fewer surgeries compared with late start of immunosuppression (> 36 months) . However, the optimal length of AZA therapy necessary to alter long term outcomes in CD is still a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
“…8,25,26 Interestingly, a recent multicentric and retrospective study with 754 patients showed that an early start of immunosuppression (< 6 months) is associated with fewer surgeries compared with late start of immunosuppression (> 36 months). 24 However, the optimal length of AZA therapy necessary to alter long term outcomes in CD is still a matter of debate. Chebli et al demonstrated a breakthrough of symptoms during continuous AZA therapy was common, particularly after 48 months on AZA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations